(untitled) (Academicia Globe: Inderscience Research, 2022)
All languages have words belonging to different groups. For example, paronyms, antonyms, synonyms and homonyms. We know that the vocabulary of these languages is growing. This article answers many questions about what paronyms are, what types they are, what their status is, and in which word groups paronyms are more common than others. Questions about how many paronyms there are in English and which phrases have the most paronyms were also answered. The article also discusses the similarities and differences between paronyms in Uzbek and English.